The Canonical Reduction Method for Symplectic Structures and Its Applications - Prykarpatsky, A.K.; Samoilenko, V.H. (Нелінійні коливання, 2001)
The canonical reduction method is analized in detail and applied to Maxwell and Yang–
Mills equations considered as Hamiltonian systems on some fiber bundles with symplectic and
connection structures. The minimum interaction principle is proved to have geometric origin
within the reduction method devised.